Professional Development In Monitoring And Evaluation And Result Utilization In Meru Region In Kenya - Cavens, Kithinji; Kidombo, Harriet; Gakuu, Christopher (European Scientific Journal, ESJ, 2016)
This study was carried out to determine the influence of professional development in Monitoring and result utilization in Meru Region; Kenya. Pragmatic approach was used to lay foundation for a mixed mode approach in methodology thus allowing for both descriptive and inferential analysis of data. The study targeted employees working in project organizations in the region and had an experience of over two years. The sample size was 218. In general, the study noted high level of M&E results utilization at project level by project employees and that Professional development activities were being carried in the region at moderate extent. Together, all activities carried out to develop professionalism in M&E had a positive high correlation thus concluding that they have influence on the actual utilization of M&E result. The study established that a unit increase in professional development in the region result to 43.6% increase in M&E result utilization. It was recommended that more of professional development activities in M&E be undertaken to include even other users of M&E result outside the Project organization to maximize on the evaluation results in order to justify the resources used in carrying M&E in organizations.